2005
DOI: 10.1086/430712
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy in Public and Private Routine Health Care Clinics in Cameroon: Lessons from the Douala Antiretroviral (DARVIR) Initiative

Abstract: A review of the hospital charts for 788 patients treated in 19 public and private clinics in Cameroon showed that clinical follow-up visits, biologic follow-up visits, and drug supply were irregular and that many patients interrupted treatment. Virological and immunologic effectiveness of therapy was as expected in patients for whom results were available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
27
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 12 publications
8
27
1
Order By: Relevance
“…These high levels of adherence confirm findings in other resource-limited settings (Byakika-Tusiime et al 2005;Fong et al 2003;Landman et al 2003;Laniece et al 2003;Laurent et al 2004;Laurent et al 2005a, b;Nachega et al 2004;Orrell et al 2003;Oyugi et al 2004;Remien et al 2003;Weidle et al 2002;Weiser et al 2003). Our findings contrast with those of Merenstein et al (2008), who found an inverse relationship between adherence and the number of children in the family.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These high levels of adherence confirm findings in other resource-limited settings (Byakika-Tusiime et al 2005;Fong et al 2003;Landman et al 2003;Laniece et al 2003;Laurent et al 2004;Laurent et al 2005a, b;Nachega et al 2004;Orrell et al 2003;Oyugi et al 2004;Remien et al 2003;Weidle et al 2002;Weiser et al 2003). Our findings contrast with those of Merenstein et al (2008), who found an inverse relationship between adherence and the number of children in the family.…”
Section: Discussionsupporting
confidence: 82%
“…While most studies have shown high levels of adherence to ART in resource-constrained settings Bisson et al 2008;Byakika-Tusiime et al 2005;Diabate et al 2007;Etard et al 2007;Fong et al 2003;Landman et al 2003;Laniece et al 2003;Laurent et al 2004;Laurent et al 2005a, b;Mills et al 2006b;Nachega et al 2004;Orrell et al 2003;Oyugi et al 2004;Remien et al 2003;San Lio et al 2008;Tadios and Davey 2006;Weidle et al 2002;Weidle et al 2006;Weiser et al 2003) there has been little discussion about how HIV? women balance the demands of adherence to HIV ART, childcare, and antiretroviral adherence among their children who are HIV-infected.…”
Section: Introductionmentioning
confidence: 99%
“…The more the number of such patients, the more the opportunities for development and transmission of drug-resistant strains of HIV. At a median period of follow-up of 14 months, LTF of nearly a third of enrollees in the public facility could be considered quite significant, and the figure is similar to those from studies of similar duration of follow-up in Cameroon, 21 Kenya, 22 and…”
Section: Discussionsupporting
confidence: 71%
“…Other studies conducted in resource-limited settings have shown that cost of ART is an insurmountable obstacle for many individuals, contributing to loss to follow-up, poor adherence to treatment, reduced ART efficacy and reduced access to HIV care, particularly for marginalized groups (Bission et al, 2006;Ivers et al, 2005;Laurent et al, 2005;Oosterhout et al, 2005). The clear way forward to avoid this obstacle is to abolish any fee associated with ART.…”
Section: Discussionmentioning
confidence: 99%